Effects of IPR by mechanical oscillating strips system on biological structures: a quantitative and qualitative evaluation - Francesca Gazzani; Denise Bellisario; Laura Fazi; Alessia Balboni; Silvia Licoccia; Chiara Pavoni; Paola Cozza; Roberta Lione (SpringerOpen, 2023)
Abstract Background To evaluate by means of profilometric analysis and scanning electronic microscope (SEM) the effects on enamel surfaces of oscillating mechanical systems for interproximal enamel reduction (IPR). Fifteen complete (Group 1) oscillating IPR sequence and 15 single metallic strips (Group 2) for active IPR phase of 0.2 mm were selected and tested on 30 freshly extracted teeth by means of tribological tests with alternative dry-sliding motion (Linear Reciprocating Tribometer, C.S.M. Instruments, Peseaux, Switzerland). Enamel surface roughness and waviness measurements were assessed by contact probe surface profiler (TalySurf CLI 2000; Taylor Hobson, Leicester, UK) and a TayMap software for the 3D analysis. Statistical analysis was performed with independent samples t-test. Significance was established at the P < .05 level. SEM analysis of enamel surfaces was conducted with a FEI Quanta 200 (Hillsboro, USA) in high vacuum at 30.00 kV. Images were acquired at 30X, 100X, and 300X of magnification. Results Teeth undergone Group 1 showed lower values of surface roughness (Ra − 0.34 µm, Rt − 1.55 µm) and significant increase of waviness parameters (Wa 0.25 µm, Wt 4.02 µm) when compared with those treated with Group 2. SEM evaluation showed smoothers and more regular surfaces when IPR was performed by complete IPR sequence. Single metallic strip determined more irregular surfaces characterized by extended grooves, alternated with enamel ridges and irregular fragments. Conclusion The adoption of a standardized oscillating IPR sequence determines more regular and harmonious enamel surfaces at the end of the procedure. An adequate polishing after IPR plays a crucial role to guarantee a good long-term prognosis and a good respect of biological structures.